The Armorial De Berry. (Scottish Section) - Clouston, J Storer (Proceedings of the Society of Antiquaries of Scotland, 1938)
The Armorial Rolls in Scotland begin comparatively late in the sixteenth century, and there is very little of definitely certain date then, till one reaches the 1540s. Before that period, however, some limited light is thrown by three of the great Continental armorials: the Armorial de Gerle, the Armorial de L'Europe and the Armorial de Berry which is the latest. It is much longer than the other two, including 125 names (not counting one repetition presumably in error), and some 93 separate families who can with reasonable confidence be identified. it has been deliberately designed to cover the greater part of the country and display a representative collection of arms for all Scotland. A detailed description of the document is given along with a list of all the Scottish names and their accompanying arms.